Unconquerable nation : knowing our enemy, strengthening ourselves - Jenkins, Brian Michael; Rand Corporation (Santa Monica, CA : RAND Corporation, 2006)
Brian Michael Jenkins presents a clear-sighted and sobering analysis of where we are today in the struggle against terrorism. Jenkins, an internationally renowned authority on terrorism, distills the jihadists' operational code and suggests how they might assess their situation very differently from how we might do so. He distills the jihadists' operational code and outlines a ferociously pragmatic but principled approach that goes beyond attacking terrorist networks and operational capabilities to defeating their entire missionary enterprise by deterring recruitment and encouraging defections. Jenkins believes that homeland security should move beyond gates and guards and become the impetus for rebuilding America's decaying infrastructure. Americans need to adopt a realistic approach to risk and get a lot smarter about security. We need to build upon the nation's traditions of determination and self-reliance. Above all, we need to preserve our commitment to American values. Preserving these values is no mere matter of morality, he argues; it is a strategic imperative. Jenkins brings to his prose the driving rhythm, no-nonsense language, passion, and energy of a warrior, and he brings to his analysis the steady, informed perspective of a historian. Unconquerable Nation is a rallying cry from a man who has dedicated his life to defending America, who has been dismayed by the propagation of homegrown terror, yet who refuses to surrender his faith in what he believes are America's finest, unconquerable values. How America deals with the terrorist threat is one of the major challenges of this century. Jenkins points the way forward.
How We Prevail -- An Appreciation of the Situation -- Knowing Our Enemy -- A Sharper Sword: Strategic Principles for Defeating Today's Enemy -- A Durable Shield: Strategies for Strengthening Ourselves.
Includes bibliographical references and index.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Terrorism -- United States -- Prevention; Terrorism -- United States